Dietary supplementation of phytoncide and soybean oil increases milk conjugated linoleic acid and depresses methane emissions in Holstein dairy cows - TaeBin Kim; MunHee Bae; JaeSung Lee; Jalil Ghassemi Nejad; HongGu Lee (Scientific Reports, 2024)
Abstract The objective of this study was to determine whether adding phytoncide oil (PO) and soybean oil (SBO) to the dairy cow diet could increase milk conjugated linoleic acid (CLA) and depress methane (CH4) emissions in Holstein dairy cows. Rumen fermentation was conducted at four levels of SBO (0, 1, 2, and 4%, on DM basis) and two levels of PO (0 and 0.1%, on DM basis) with in vitro experiment. To evaluate blood parameters, fecal microbe population, milk yield and fatty acid compositions, and CH4 production, in vivo experiment was conducted using 38 Holstein dairy cows divided into two groups of control (fed TMR) and treatment (fed TMR with 0.1% PO and 2% SBO as DM basis). In the in vitro study (Experiment 1), PO or SBO did not affect rumen pH. However, SBO tended to decrease ruminal ammonia-N (p = 0.099). Additionally, PO or SBO significantly decreased total gas production (p = 0.041 and p = 0.034, respectively). Both PO and SBO significantly decreased CH4 production (p < 0.05). In addition, PO significantly increased both CLA isomers (c9, t11 and t10, c12 CLA) (p < 0.001). Collectively, 0.1% PO and 2% SBO were selected resulting in most effectively improved CLA and decreased CH4 production. In the in vivo study (Experiment 2), 0.1% PO with 2% SBO (PSO) did not affect complete blood count. However, it decreased blood urea nitrogen and magnesium levels in blood (p = 0.021 and p = 0.01, respectively). PSO treatment decreased pathogenic microbes (p < 0.05). It increased milk yield (p = 0.017) but decreased percentage of milk fat (p = 0.013) and MUN level (p < 0.01). In addition, PSO treatment increased both the concentration of CLA and PUFA in milk fat (p < 0.01). Finally, it decreased CH4 emissions from dairy cows. These results provide compelling evidence that a diet supplemented with PSO can simultaneously increase CLA concentration and decrease CH4 production with no influence on the amount of milk fat (kg/day) in Holstein dairy cows.